Beam Positions Optimization to Achieve Improved CT Images with Limited Data - Rena Widita (Journal of Mathematical and Fundamental Sciences, 2006)
In radiotherapy planning, margins are used to account for the uncertainties due to internal organ and patient motion as well as set-up error. Improvement in radiotherapy treatments may be achieved by reducing the set-up uncertainty and thus treatment margins allowing a higher dose to be delivered to the target volume. It is important to be able to verify the success of the treatment by determining the position of patient and the dose deposited in the patient at each fraction. One possibility for achieving this would be to collect limited information while the patient is on the treatment couch. The aim of this study is to develop a method for determining intelligent angles to use to reconstruct an image for dose verification.A method optimizing the angles based on an objective function is required. The methods developed here are based on image correlation and projection correlation that have been investigated previously. Two optimization methods, deterministic and stochastic (simulated annealing), were also assessed. The effectiveness and practicality of each of these combinations were compared.